FRI0193 Current therapy of rheumatoid arthritis in turkey: rheumatologists' perspective. (23rd January 2014) - Kamali, S.; Pay, S.; Inanc, N.; Simsek, I.; Hamuryudan, V.
Abstract : Background: Synthetic (s) and biologic (b) DMARD's licensed for RA, such as hydroxychloroquine (HCQ), sulfasalazine (SSZ), methotrexate (MTX), leflunomide (LEF) and biologics including TNF-alpha inhibitors (TNF-i) and Rituximab (RIT), can be prescribed according to the rules defined by Ministry of Health, in Turkey. Objectives: We aimed to demonstrate the current approach to RA treatment of internist rheumatologists by a survey analysis Methods: The survey being prepared by four rheumatologists (SK, SP, NI, IS) and consists of 74 questions related to the treatment options (part I) and evaluation of the treatment efficacy (part II), opened for electronic evaluation in "Turkish Rheumatology Society" web site, with the support of Pfizer Inc. Part I was comprised of 56 questions and answers established as "yes/no" or "multiple choises" regarding to glucocorticoid (GC), s and b-DMARD (excluding Orencia which was not licensed at that time) treatment strategies Results: Eighty-one rheumatologists including academicians (51%), specialists (26%), and residents (23%), mainly (75%) from university hospitals, completed the survey. The patients' compliance (60%) and reimbursement rules (42%) were found as the main factors affecting the treatment decision. The frequency of GC prescription was 99% in remission induction (RI) (48%>7, 5-15 mg/d, 34%>≤7, 5 mg/d), and 80% in maintenance of remission (RM) (%65 ≤5 mg/d). MTX has been preferred by oral route in 95% in RI and 98% in RM along with folic acid supplementation (99%) (5-10 mg/w). sDMARD monotherapy (83% MTX, 15% HCQ, 2% SSZ) has been preferred in 64% of early-mild and 5% (only MTX) in moderate to severe RA. Combined s-DMARDs were reported to be commenced in 36% of early-mild (88% MTX+HCQ), 95% of moderate to severe RA (63% MTX+SSZ+HCQ) and in 99% of severe deforming RA (51% MTX+SSZ+HCQ, 47% MTX+LEF). Comorbidities (80%) and disease activity (65%) were the main patient related concerns for b-DMARD decision. Feasibility of drug appliance was the most frequent factor for the pysicians' choise of biologic drug. TNF-i usage in severe-deforming RA was as frequent as in early RA. Cost of drug, infections and malignancy potential were te main concerns for TNF-i therapy. Rheumatologists' were tend to switch to another TNF-i (53%) in the presence of TNF-i resistance. RIT has been the most prescribed biologic when compared to TNF-i (88% vs 43%) in RA complicated with interstitial lung disease. Conclusions: Current treatment approach to RA of internist rheumatologists was found to be accorded with the international guidelines. MTX was the most prescribed drug for both mono and combo treatment protocols. Combination of s-DMARDs was the initial treatment option for the early resistant and advanced RA. Comorbidities, disease activity, functional status and easy applicability of drug were the principal concerns for the decision of commence to TNF-i and choise of TNF-i. Infection was the main concern for the maintenance of TNF-i. Disclosure of Interest: None Declared